Social data analytics : collaboration for the enterprise - Krishnan, Krish; Rogers, Shawn P. (Morgan Kaufmann, 2015)
This is a guide for professionals who want to employ social data for analytics and business intelligence (BI). This book provides a comprehensive overview of the technologies and platforms and shows you how to access and analyze the data. You'll explore the five major types of social data and learn from cases and platform examples to help you make the most of sentiment, behavioral, social graph, location, and rich media data. A four-step approach to the social BI process will help you access, evaluate, collaborate, and share social data with ease. It provides foundational understanding of new and emerging technologies-social data, collaboration, big data, advanced analytics; includes case studies and practical examples of success and failures; will prepare you to lead projects and advance initiatives that will benefit you and your organization.--